PHARMACOKINETIC STUDIES OF OFLOXACIN FOLLOWING ORAL ADMINISTRATION IN GOATS - H. BARUAH,; D. C. ROY,; R. K. ROY,; J. SARMA,; L. C. LAHON,; S. KHARGHARIA, (The Bioscan, 2015)
The pharmacokinetics of Ofloxacin was estimated following single oral administration in goats to compute a rational dosage regimen. HPLC and non-compartmental open model was used to determine the plasma Ofloxacin concentration and to calculate kinetic parameters resepectively. The therapeutic concentration was achieved in 45 min and maintained up to 8 h. The Cmax, tmax, AUC and AUMC values were 1.168 ± 0.07 mg/ mL, 5.17 ± 0.72 h, 11.41 ± 1.13 m/h/mL and 221.11 ± 38.44 mg/h/ml respectively. The mean absorption half life (t1/2 ka) and mean absorption time (MAT) of 5.40 ± 0.78 h and 7.79 ± 1.13 h respectively. In goats, Ofloxacin showed poor bioavailability with a value of 24.14 ± 1.70 % and slow elimination with mean residence time (MRT) of 16.05 ± 1.19 h. Keeping in view of the above kinetic parameters of Ofloxacin, a rational loading dose of 21 mg/kg followed by the maintenance dose of 13 mg/kg at 24 h dosing interval by oral route can recommended in goats.